2002
DOI: 10.1148/radiol.2231010734
|View full text |Cite
|
Sign up to set email alerts
|

Covered, Retrievable, Expandable Urethral Nitinol Stent: Feasibility Study in Dogs

Abstract: Although some design modifications are necessary to reduce current complications, the polyurethane-covered retrievable nitinol stent seems feasible for use in the urethra. Stent-induced granulation tissue formation improved after stent removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
0
11
0
5
Order By: Relevance
“…In spite of this, we hasten to underscore our observation of resolution of stent-induced stenosis in all cases after stent removal. Of note, this pattern of normalization of hyperplastic tissue growth after stent removal has also been documented in cases of urethral strictures [23,24]. We thereby encourage a greater threshold of stent removal in cases of mild to moderate severity of tissue hyperproliferation only so long as the patient is capable of tolerating a soft diet and regular follow-up is possible.…”
Section: Discussionmentioning
confidence: 55%
“…In spite of this, we hasten to underscore our observation of resolution of stent-induced stenosis in all cases after stent removal. Of note, this pattern of normalization of hyperplastic tissue growth after stent removal has also been documented in cases of urethral strictures [23,24]. We thereby encourage a greater threshold of stent removal in cases of mild to moderate severity of tissue hyperproliferation only so long as the patient is capable of tolerating a soft diet and regular follow-up is possible.…”
Section: Discussionmentioning
confidence: 55%
“…Both balloon-expandable (BEMSs) and self-expanding metallic stents (SEMSs) are generally used for relieving urinary obstruction in dogs [2,3,7,10,11,18,19]. The major advantage of BEMSs is lack of the foreshortening that occurs with some types of SEMSs, although BEMSs relatively lack flexibility and elasticity.…”
mentioning
confidence: 99%
“…Another study using polyurethane covered wire stents with paclitaxel-eluting coatings found much favorable clinical outcome in dogs [11,17]. Main complications associated with urethral stent placement in dogs are luminal re-stenosis by epithelia hyperplasia resulting from stent placement, re-obstruction resulting from either a blood clot or mucosal swelling and edema secondary to excessive balloon dilatation and presumptive urethral mucosa trauma or tearing and development of urinary incontinence resulting from the damage to urethral sphincter by stent placement [2,3,7,10,11,18,19]. Unfortunately, no concrete study related to urethral stent placement in cats has been conducted yet.…”
mentioning
confidence: 99%
“…Although some authors reported that endoscopic or surgical removal of uncovered urethral stents were feasible [2, 4-6, 8, 9], removal failure and risk of incomplete removal or significant bleeding have occurred in cases of tight stent welding to the urethral wall [2,8]. In contrast, covered retrievable stents are not as affected by ingrowth of tissue hyperplasia into the stent wire mesh as far as the covering material is intact and are thus easily removed when no longer necessary or there are complications [10][11][12].…”
Section: Discussionmentioning
confidence: 99%